The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18632/oncotarget.11170
|View full text |Cite
|
Sign up to set email alerts
|

A recombinantly tailored β-defensin that displays intensive macropinocytosis-mediated uptake exerting potent efficacy against K-Ras mutant pancreatic cancer

Abstract: K-Ras mutant pancreatic cancer cells display intensive macropinocytosis, indicating that this process may be exploited in the design of anticancer targeted therapies. In this study, we constructed a macropinocytosis-oriented recombinantly tailored defensin (DF-HSA) which consists of human β-defensin-2 (DF) and human serum albumin (HSA). The macropinocytosis intensity and cytotoxicity of DF-HSA were investigated in K-Ras mutant MIA PaCa-2 cells and wild-type BxPC-3 cells. As found, the DF-HSA uptake in MIA PaCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The mice were sacrificed at 20 d after inoculation, and solid tumors were dissected, measured and photographed. At the end of the experiment, the fresh tumor tissue specimens were collected for immunohistochemical analyses using antibodies specific for CDK11 p110 and Ki67 (1:1000 dilution, Servicebio Technology Co., Ltd., #GB13030-2) as described previously [29].…”
Section: In Vivo Subcutaneous Xenograft Modelsmentioning
confidence: 99%
“…The mice were sacrificed at 20 d after inoculation, and solid tumors were dissected, measured and photographed. At the end of the experiment, the fresh tumor tissue specimens were collected for immunohistochemical analyses using antibodies specific for CDK11 p110 and Ki67 (1:1000 dilution, Servicebio Technology Co., Ltd., #GB13030-2) as described previously [29].…”
Section: In Vivo Subcutaneous Xenograft Modelsmentioning
confidence: 99%
“…Western blotting was used to detect the expression levels of the protein EGFR with the corresponding antibodies. H520 cells were plated into 100-mm dishes at the density of 5×10 5 and grown to 70-80% confluence, after which the cells were washed three times in PBS and cultured for 12 h in serum-free medium. Cells were incubated with Ec-LDP(AE)-DF (0.1, 0.5, or 1 nmol/L) at 37°C for 24 h, followed by stimulation with EGF (Abcam, 50 ng/mL), or both at 37°C for 30 min.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…Additionally, they may also be involved in adaptive immunity by serving as chemo-attractants and activators of the immune cells [3,4]. Previous studies have shown that human defensins have antibacterial activity, antiviral activity and tumor cell cytotoxicity [5]. Compared with traditional chemotherapeutics, defensins would potentially have a therapeutic advantage in that it is difficult for cancer cells to develop drug resistance; in addition, defensins show no immunogenicity and are resistant to proteolysis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, human beta-defensin-2 (hBD-2) have been shown to also reduce the viability of melanoma cells through the downregulation of BRAF ( 52 ). Besides their natural derivatives, synthetic defensin analogs may be designed for greater anticancer efficacy: Du et al demonstrated that recombinant tailored defensin (DF-HSA) comprising human β-defensin-2 (DF) and human serum albumin (HSA) was more effective than natural β-defensin at curbing the proliferation of K-Ras-mutant MIA PaCa-2 cells and suppressing the growth of a pancreatic carcinoma xenograft ( 53 ).…”
Section: Major Therapeutically Relevant Classes Of Ampsmentioning
confidence: 99%